2019
DOI: 10.1136/bmjopen-2018-027456
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment persistence of golimumab in the management of immune-mediated rheumatic diseases in Europe: a systematic literature review

Abstract: ObjectivesTo summarise real-world data from studies reporting golimumab persistence in European immune-mediated rheumatic disease (IMRD) populations and to report pooled estimates.DesignSystematic literature review.Data sourcesRelevant literature was identified through searching Medline and Embase via Ovid as well as the conference databases of European League Against Rheumatism and American College of Rheumatology—Association of Rheumatology Health Professionals.Eligibility criteriaWe screened records using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…This notion is supported by the analyses demonstrating a cost-effectiveness of golimumab therapy among patients with PsA and AS [18,19]. Furthermore, a recent systematic review of 12 studies showed that patients treated with golimumab had higher persistence when compared with other anti-TNF treatments, especially in RA and PsA setting [20]. Therefore, use of golimumab might reduce HCRU also due to a high long-term persistence among the patients with rheumatic diseases using this medication.…”
Section: Discussionmentioning
confidence: 87%
“…This notion is supported by the analyses demonstrating a cost-effectiveness of golimumab therapy among patients with PsA and AS [18,19]. Furthermore, a recent systematic review of 12 studies showed that patients treated with golimumab had higher persistence when compared with other anti-TNF treatments, especially in RA and PsA setting [20]. Therefore, use of golimumab might reduce HCRU also due to a high long-term persistence among the patients with rheumatic diseases using this medication.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to SEC, multiple patient registries and observational cohort studies have examined the survival of different anti-TNFs in biologic-experienced (mainly anti-TNFs) patients. In these studies, the 1 year drug survival ranged widely from 51 to 77% (12,(20)(21)(22)(23)(24)(25)(26)(27). Nevertheless, real life data comparing directly anti-TNF and anti-IL17 (SEC) drug survival are missing.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recently published systematic literature review [25], in 12 real-world studies comparing various TNFi treatments of immunemediated rheumatic diseases, GLM persistence was found to be significantly better than or equal to the persistence of its comparators. In conclusion, overall GLM persistence (regardless of treatment line) at 24 months approximated 50%, with a lower persistence in AS (43%) patients than in RA and PsA.…”
Section: Discussionmentioning
confidence: 99%